If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2(y + -6) = 20 Reorder the terms: 9 + 2(-6 + y) = 20 9 + (-6 * 2 + y * 2) = 20 9 + (-12 + 2y) = 20 Combine like terms: 9 + -12 = -3 -3 + 2y = 20 Solving -3 + 2y = 20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2y = 20 + 3 Combine like terms: -3 + 3 = 0 0 + 2y = 20 + 3 2y = 20 + 3 Combine like terms: 20 + 3 = 23 2y = 23 Divide each side by '2'. y = 11.5 Simplifying y = 11.5
| -6-11x=7x-12 | | 2x^2+56x-29=0 | | (4u+7)(6-u)=0 | | 7y=28y+6 | | 2z^2-17z+30= | | -9+5x=-14 | | -6=-3r | | (Y+5)+x=2.5y | | 70-3x=90-43x | | 3z^3*z= | | 9+3q=12+2q | | 11v-9v=4 | | 70-3x=90-11x | | (9x+12y)(9x-12y)= | | (Y-5)+x=2.5y | | 5(c-4)=6(c-5) | | log(x)-log(x+11)=-1 | | 3m-29=-44+8m | | 5(x+10)=7x-32 | | 4800000=2900000+1600x | | 3x^2+32x+20= | | -20-2x=-30 | | 6m-5=-23+9m | | -30=-84 | | 5y-4+y+30=8y+30-4y | | 3(3x+7)-7=18x+1-9x | | 2[3(X+y)-4(6x-5y)]= | | 6m-5=23+9m | | -(x-7y)-2(2y-5x)=0 | | 3(x+3)-2=3x+2 | | 3x(x^3+6)= | | 20x+25x=180 |